FORMULASI SEREAL FLAKES BERBASIS TEPUNG TALAS (COLOCASIA ESCULENTA L.), BENGKUANG, WORTEL DAN TEPUNG JAGUNG SEBAGAI PRODUK PANGAN SEHAT RENDAH GLUTEN - Diah Kusuma Wardhani; Astuti, Siswi (jurnal ATMOSPHERE, 2025)
Autism cases are increasing so sufferers need balanced nutrition and gluten-free consumption. This study aims to develop Flakes cereal made from taro flour, corn flour, jicama and carrot flour as a healthy food product low in gluten for autism sufferers. Taro flour was chosen because it contains carbohydrates, dietary fiber, and gluten-free flour, corn flour in the form of carbohydrates and gluten-free, jicama and carrots have vitamins that enrich the nutrition of Flakes cereal. This formulation has a ratio of taro flour and corn flour (gr) of 70:30, 60:40, 50:50, 40:60, 30:70 and a ratio of jicama and carrots (gr) of 1:9, 2:8, 3:7, 4:6, 5:5. The analysis was carried out through hedonic tests and physicochemical tests. The best results of the variable 30:70 (1:9) with organoleptic values ​​for color 4.65, aroma 3.85, taste 4.20, texture 4.55, and preference 4.45, water content and ash content of 1.05% and 0.05% according to SNI Flakes. The results of the study are expected to encourage innovation of local food with high nutrition and diversification of healthy food.